The Principal's Strategy In Improving The Quality Of Teacher Performance In The Learning Process At The Integral Islamic Elementary School Lukman Al-Hakim Situbondo - Musdalifah Alwi (JOSSE: Journal of Social Science and Economics, 2022)
This research is motivated by the learning conditions in schools which have decreased due to the pandemic situation which requires students to study at home to reduce the spread of the co-19 virus chain. The principal's strategy plays a very important role in the success of educational goals. In addition, the advantages of this school are the development of material on memorizing the Qur'an which involves many teachers with different teaching styles, especially in the context of forming the noble character of students. Such things affect the teacher's performance to realize the mission and mission of the school. The purpose of this study was to analyze and describe: the quality of teacher performance in the learning process, the principal's strategy in improving the quality of teacher performance as well as what factors influence the performance of school principals in improving the quality of teacher performance in the learning process at SD Islam Integral Lukman Al-Hakim Situbondo. This study uses qualitative methods using data collection techniques with observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. From the results of the study, it can be concluded that the quality of teacher performance has decreased due to the pandemic period which limited the space for interaction in teaching and learning activities (KBM), the principal's strategy is very influential and needed in improving teacher performance in the learning process. And there are several inhibiting factors in the implementation of the principal's strategy.